The Impact of Venture Capital on Innovation Behaviour and Firm Growth - Michael Peneder (Austrian Institute of Economic Research (WIFO), 2010)
Proposing a novel research design for firm-level impact studies, I investigate the effects of venture capital financing on corporate performance by applying a two-stage propensity score matching on Austrian micro-data. Controlling for differences in industry, location, legal status, size, age, credit rating, export and innovation behaviour, the findings (i) assert the financing function of venture capital, showing that recipients lacked access to satisfactory alternative sources of capital; (ii) identify selection effects, where venture capital is invested in firms with high performance potential; and finally (iii) confirm the value adding function in terms of a genuine causal impact of venture capital on firm growth, yet not on innovation output.
Keywords: 330; venture capital; entrepreneurship; firm growth; propensity score matching; Risikokapital; Unternehmensgründung; Unternehmenswachstum; Innovationsmanagement; Österreich